2014
DOI: 10.1590/0004-282x20140016
|View full text |Cite
|
Sign up to set email alerts
|

ENCOMS: Argentinian survey in cost of illness and unmet needs in multiple sclerosis

Abstract: The objective of the study was to assess the cost of multiple sclerosis (MS) patients in Argentina categorized by disease severity using a societal perspective. Method: Cross-sectional study including MS patients from 21 MS centers in 12 cities of Argentina. Patients were stratified by disease severity using the expanded disability status scale (EDSS) (group 1 with EDSS score between 0 and 3; group 2 with EDSS .3 and ,7; group 3 with EDSS $7). Direct and indirect costs were analyzed for the second quarter of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Our initial search, conducted on 5 October 2019, retrieved 1099 records, of which only 11 articles [ 43 53 ] were deemed eligible. The COI study conducted in Russia was reported in two articles [ 13 , 47 ], and we excluded the article that presented the results of 16 mostly high-income European countries [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our initial search, conducted on 5 October 2019, retrieved 1099 records, of which only 11 articles [ 43 53 ] were deemed eligible. The COI study conducted in Russia was reported in two articles [ 13 , 47 ], and we excluded the article that presented the results of 16 mostly high-income European countries [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Backward and forward reference searching found no additional studies. As categorized according to the method for calculating costs of MS, eight of the 14 identified studies used a BU approach [ 43 48 , 54 , 55 ], and six used a TD approach [ 49 53 , 56 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations